2020
DOI: 10.3390/molecules25061296
|View full text |Cite
|
Sign up to set email alerts
|

PNA-Based MicroRNA Detection Methodologies

Abstract: MicroRNAs (miRNAs or miRs) are small noncoding RNAs involved in the fine regulation of post-transcriptional processes in the cell. The physiological levels of these short (20–22-mer) oligonucleotides are important for the homeostasis of the organism, and therefore dysregulation can lead to the onset of cancer and other pathologies. Their importance as biomarkers is constantly growing and, in this context, detection methods based on the hybridization to peptide nucleic acids (PNAs) are gaining their place in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 116 publications
0
32
0
Order By: Relevance
“…Employing PNA in cells or tissues is more challenging, as the matrix becomes increasingly complex, more extensively modified PNAs are required to facilitate solubility and cellular uptake while maintaining selectivity. As a result, PNA has been found to have many applications as a research and diagnostic tool both in the lab and in the clinic [7][8][9], while advancement of PNA therapeutics, especially when compared to other nucleic acid derivatives [10,11], has notably lagged behind. To better understand the potential of PNA-based technologies, we will examine selected research and diagnostic applications highlighting the versatility of PNA as well as key limitations that hinder the extension of these technologies to therapeutic applications.…”
Section: Pna Probes For Research and Diagnostic Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Employing PNA in cells or tissues is more challenging, as the matrix becomes increasingly complex, more extensively modified PNAs are required to facilitate solubility and cellular uptake while maintaining selectivity. As a result, PNA has been found to have many applications as a research and diagnostic tool both in the lab and in the clinic [7][8][9], while advancement of PNA therapeutics, especially when compared to other nucleic acid derivatives [10,11], has notably lagged behind. To better understand the potential of PNA-based technologies, we will examine selected research and diagnostic applications highlighting the versatility of PNA as well as key limitations that hinder the extension of these technologies to therapeutic applications.…”
Section: Pna Probes For Research and Diagnostic Applicationsmentioning
confidence: 99%
“…With miRNAs identified as increasingly prominent players in regulating gene expression, detection and quantification of these species is critical to deepening our understanding of miRNAs relation to disease. PNA-based fluorescence and electrochemical sensors of miRNAs have seen increasing use in a number of applications as highlighted in a recent review [9]. Early attempts at miRNA detection mirrored those of mRNA, using in situ enzymatic amplification to generate an optical signal [270].…”
Section: Detection Of Micrornasmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptide nucleic acids (PNAs) are DNA mimics with neutral polyamide backbone and have gained a lot of attention as alternatives to DNA probes, in particular for short NA sequences such as micro-RNAs (20-22 mers) that are unlikely to be effectively amplified [49]. Here, the polyamide backbone in PNA probes enables the formation of a PNA-RNA duplex with higher binding strength than those of RNA-RNA or DNA-RNA.…”
Section: Recognition Strategiesmentioning
confidence: 99%
“…These RNAs may be in the form of mRNAs [ 20 ], lncRNAs [ 21 ], miRNAs, and others. An excellent review in this Special Issue, reported by Cadoni et al [ 22 ], describes the various methodologies used in conjunction with PNA to detect miRNAs. Changes in miRNA expression are associated with a variety of diseases and therefore these miRNAs are considered as ideal disease biomarkers.…”
mentioning
confidence: 99%